THE EFFECT OF MIND MAPPING TECHNIQUE ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMPN 8 PEKANBARU IN WRITING DESCRIPTIVE TEXTS - Ilham Rivaldi; Atni Prawati; Novitri Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is aimed to find out whether or not there is significant effect of Mind Mapping Technique on the Ability of the First Year Students of SMPN 8 Pekanbaru in Writing Descriptive Texts. The research design is a pre-experimental research with one group pre-test and post-test design. The sample was VII-3 chosen by using cluster random sampling technique. In order to collect the data, the pre-test and post-test were administered and then the data were statistically analyzed by using the t-test formula. The result showed that the mean score of post-test was higher than mean score of pre-test (67.14 > 59.24). The value of t-test was 12.523 while the value of t-table in significance level 5% df = 35 was 2.030. Since the value of the t-test was higher than t-table, it can be concluded that Alternative Hypothesis (Ha) was accepted and Null Hypothesis (Ho) was rejected. It means that there was significant effect of Mind Mapping Technique on the Ability of the First Year Students of SMPN 8 Pekanbaru in Writing Descriptive Texts.Key Words: Effect, Mind Mapping, Writing Ability, Descriptive Text